Seasonal and spatial distributions of biofilm proxy parameters across an intertidal area at St. Lawrence Estuary, Canada - Waqas, Atif; Neumeier, Urs; Rochon, André (PANGAEA, 2020)
The biofilm influence on sediment stabilization was determined by quantifying pigment contents (Chlorophyll a and Phaeopigments) and extra polymeric substances (EPSSaline, EPSEDTA) in surface sediment at Nazareth tidal flat and marsh located west of Rimouski on the southern shore of Lower St. Lawrence Estuary (Canada). Small sediment cores (n=3) were taken using 60 ml syringes (36 mm ϕ) and preserved in liquid nitrogen until further processing. The cores were sectioned on a cryo-macrotome (Leica CM3600 XP) in 1 mm slices down to 3 mm. Multiple field campaigns were conducted at three cross shore transects (A, B, C) in summer 2016 (8, 9, 10 August), summer 2017 (23, 24, 25 August), with subsequent campaigns at B Transect in autumn 2017 (22, 25 November), winter 2018 (16, 20 February), spring 2018 (30 May), and summer 2018 (6 September). The data presented here does not contain the summer field campaigns, which was published in the context of annual variations in sediment biostabilization (Waqas et al., 2019, https://doi.org/10.1594/PANGAEA.911765).
Keywords: Biofilms; Biostabilization; Intertidal cohesive sediments